STEAM-Integrated PjBL Learning Tools for Newton’s Laws to Improve High School Students’ Creative Thinking Skills - Dea Ramadhana Zsa Zsa Alifah; Titin Sunarti; Oka Saputra; Hanandita Veda Saphira (Jurnal Pendidikan Fisika, 2026)
Creative thinking skills are essential competencies in physics education because students are expected not only to understand scientific concepts but also to apply them creatively in solving contextual problems. However, learning in physics on Newton’s Laws is often still dominated by routine problem-solving and formula-based instruction, which provides limited opportunities for students to develop fluency, flexibility, originality, and elaboration. This study aimed to develop and evaluate STEAM-integrated Project-Based Learning (PjBL) learning tools on Newton’s Laws to improve students’ creative thinking skills. This research employed a Research and Development design using the 4-D model, consisting of Define, Design, Develop, and Disseminate stages, with dissemination limited to classroom implementation and academic reporting. The developed products included a teaching module, student worksheets, and a creative thinking skills test instrument. The study involved 55 eleventh-grade science students at SMA Labschool UNESA 1 Surabaya, selected through purposive sampling. Data were collected through expert validation, learning implementation observation, pre-test and post-test, and student response questionnaires. Data were analyzed using descriptive statistics, normalized gain, and a paired t-test. The results showed that the developed learning tools were very valid, with an average validation score of 88.30%. The effectiveness test indicated a substantial increase in students’ creative thinking skills, with the pre-test average increasing from 38.14 to 89.86 in the post-test, an n-gain score of 0.85 in the high category, a significant paired t-test result (Sig. < 0.05), and positive student responses of 85%. The novelty of this study lies in the explicit integration of PjBL syntax, STEAM components, and indicators of creative thinking into structured learning tools for Newton’s Laws. These findings indicate that the developed learning tools are valid, practical, and effective, and that they contribute to physics education by offering a contextual, interdisciplinary, and student-centered instructional design to foster creative thinking skills.